If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -6) = 3c Reorder the terms: 4(-6 + 2x) = 3c (-6 * 4 + 2x * 4) = 3c (-24 + 8x) = 3c Solving -24 + 8x = 3c Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + 8x = 24 + 3c Combine like terms: -24 + 24 = 0 0 + 8x = 24 + 3c 8x = 24 + 3c Divide each side by '8'. x = 3 + 0.375c Simplifying x = 3 + 0.375c
| 73*10+6+-13=723 | | 73*10+6-13=723 | | 4c+4d+2c-8d= | | z+2iz=2i+1 | | 9x-100=3x-10 | | -3-4x=5-6x | | 36/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4/0.4=0 | | 3x+9=31-5x | | 36/0.4=1231 | | 36/0.4=0 | | -1-4x=5-6x | | 16-4[9-3(2x-5)]=-4(3-6x) | | 7x*12y=2a*12b | | 3-4x=5-6x | | x+12=13-x | | 2x+12=6-4x | | x-4=2x-17+9 | | 4sinx=-cos^2x+4 | | 45y=15 | | 12*(x^17)=60 | | 1-5[7+2(3x-1)]=-6(4+5x) | | 1111=100 | | 42-9y=33 | | 5-kx=2k-x^2 | | x^2-kx-2k+5=0 | | m=2/3(-5,5) | | 5n+67=8n-11 | | X-2X/100=600 | | 5+2x=x+13 | | (x4y2_3x3y-5xy_6)$(x2y_2xy-2)/ | | 10/6=x | | 3x+8x-7x= |